Genome-Wide Identification, Phylogeny, and Expressional Profiles of the Mitogen-Activated Protein Kinase Kinase Kinase (MAPKKK) Gene Family in Pyropia yezoensis - Kong, Fanna; Cao, Min; Li, Na; Sun, Bin; Sun, Meijuan; Mao, Yunxiang (Frontiers in Marine Science, 2020)
Mitogen-activated protein kinase kinase kinases (MAPKKKs) are pivotal components of MAPK cascades. Pyropia yezoensis, belonging to Rhodophyta, is an important macroalga growing in the intertidal zone of temperate Japan and China. At present, little is known about MAPKKKs and their potential regulatory mechanisms in response to environmental stressors in red algae, particularly with regard to how this gene family retained its ancient characteristics. In this study, we identified 33 MAPKKK genes in P. yezoensis by bioinformatics analysis. Phylogenetic analysis classified them into Raf, MEKK and ZIK groups, which contained conserved kinase motif with minor variations. The number of intron of all PyMAPKKK is few, up to 3. Regulatory elements prediction indicated that the cis-acting elements included many motifs involved in the stress response. Furthermore, expression analysis of PyMAPKKKs under different stress conditions revealed that numerous PyMAPKKK genes were involved in various signaling pathways with different expression patterns. Additionally, 16 PyMAPKKK genes were validated their expression patterns by Realtime-PCR analysis. An interactome network of PyMAPKKK was constructed to show that most of the interacting proteins were serine/threonine protein kinases, MAPKs, and ubiquitin-binding proteins. Our study provided helpful information for understanding the evolution and function of the MAPKKK family in P. yezoensis.